RETRACTED: On the issue of mathematical modeling of the interaction of phases in energy-packed heat and mass transfer devices - Ismailov Bakhtiyar; Babakhodzhaev Raximjon; Kuchkarov Akmaljon; Mamatov Olmos; Ismailov Khayrullo; Hamdamov Diyorbek; Qipchaqova Gavxar (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001